Самооценка коммуникативной компетенции педагогов ДОУ - Sorokovikova I. V., Soloviova N. A. (Студенческая наука XXI века, 2016)
In article the problem of formation and development of communicative competence of teachers of preschool educational institution is covered, characteristic signs of high level of communicative competence are presented, criteria and indicators of different levels of development of this competence are presented. Besides results of research of teachers of preschool educational institution on identification of levels of development of communicative competence are presented and analysed.
Keywords: компетенция; компетентность; коммуникативная компетентность